Salmonella enterica serotype Typhi infection and miscarriage in pregnancy: Are we missing the geographic demon? - Sujata Lall; Nidhi Goel; Vani Malhotra; Aparna Parmar (Journal of Clinical and Scientific Research)
Salmonella enterica serotype typhi is a Gram-negative, rod-shaped, flagellated and facultative intracellular bacterium. We present the case of maternal S. typhi infection leading to second-trimester miscarriage. A 26-year-old tertigravida with 25 weeks of pregnancy presented with leaking and copious discharge per vaginum for 10 h and intermittent fever for 2 days. She also gave history of intermittent episodes of severe diarrhoea, pain in the right hypochondrium and high fever for 4 weeks. There was a history a previous miscarriage at 16 weeks. Abdominal ultrasonography was consistent with absent liquor. She delivered a neonate who succumbed to a low Apgar score of 3/10 and expired within 3 h. A high vaginal swab (HVS) taken during the placental exploration grew S. typhi on pyogenic culture. The Widal test was reactive for S. typhi antibody TO-somatic antigen at a dilution of 1:160 and S. typhi antibody flagellar antigen (TH) at a dilution of 1:320. With the evidence of isolation of S. typhi from HVS and titres of H and O in the Widal, vertical transmission was considered. S. typhi infection should be considered in the differential diagnosis of a pregnant female presenting with complaints of fever and diarrhoea in endemic countries like India with a high index of clinical suspicion.